Optimalisasi Potensi Limbah Alat Gelas sebagai Adsorben Limbah Logam Berat Fe, Cd, Pb dan Mn Skala Laboratorium - Melisa Weno Gusthia; Fatiyah Aghni Yati Nurmi; Sefina Rahmatunisa; Mulda Muldarisnur (Jurnal Fisika Unand, 2026)
Chemical laboratory activities produce liquid waste containing hazardous materials, including heavy metals such as Fe, Cd, Pb, and Mn, which have the potential to pollute the environment if not managed properly. This study aims to optimize the use of laboratory glassware waste as an environmentally friendly alternative adsorbent to reduce heavy metal levels in laboratory-scale liquid waste. The research stages include collecting glassware waste from various laboratories, grinding, sieving, and activating the adsorbent through chemical treatment (HNO₃ and HCl-HNO₃), drying, calcination, and adding NaOH to open the adsorbent pores. Material characterization was carried out using SEM, FTIR, and BET to observe the morphology and surface area of the pores. Initial results showed that the three-stage activation was able to improve the quality of the adsorbent pores so that it was ready for use in the adsorption process. In the next stage, heavy metal adsorption tests were carried out with variations in time and mass of the adsorbent, then analyzed using Flame AAS and re-characterized with SEM-EDX, FTIR, and BET. The results using FTIR can be proven that the adsorbent contains SiO2 compounds that have the potential to have pores due to the structure of the compound. The results of the BET characterization obtained a surface area value of 0, which proves that the adsorbent has a very small pore size, also called micropores. The results of Flame AAS measurements show that the adsorbent is able to adsorb heavy metals with an adsorption percentage above 85%.